Neprilysin inhibition does not alter dynamic of proenkephalin‐A 119‐159 and pro‐substance P in heart failure. (20th March 2021) - Arfsten, Henrike; Goliasch, Georg; Bartko, Philipp E.; Prausmüller, Suriya; Spinka, Georg; Cho, Anna; Novak, Johannes; Mascherbauer, Julia; Haslacher, Helmuth; Strunk, Guido; Hülsmann, Martin; Pavo, Noemi
Abstract: Aims: As NEP degrades many substrates, the specific therapeutic mechanism of NEP inhibition with angiotensin receptor neprilysin inhibitor (ARNi) in heart failure with reduced ejection fraction (HFrEF) is not entirely evident. The aim of this study was to investigate the response of two substrates of NEP—the tachykinin and enkephalin systems—to the initiation of ARNi therapy in HFrEF. Methods and results: Between 2016 and 2018, 141 consecutive patients with stable HFrEF [74 with initiation of ARNi and 67 controls on continuous angiotensin converting enzyme inhibitor (ACEi) or angiotensin receptor blocker (ARB) therapy] were prospectively enrolled. Plasma proenkephalin‐A 119‐159 (PENK) and pro‐substance P (pro‐SP) were serially determined. Proenkephalin‐A 119‐159 and pro‐SP correlated strongly with each other ( rs = 0.67, P < 0.001) and kidney function ( rs = −0.66, P < 0.001 and rs = −0.54, P < 0.001) and modestly with NT‐proBNP ( r s = 0.32, P < 0.001 and r s = 0.24, P = 0.006, respectively). Concentrations of circulating PENK were slightly elevated after 1 and 2 year follow‐up compared with baseline (BL) [BL median: 67.4 pmol/L (IQR: 57.3–89.8), 1 year: 83.5 pmol/L (IQR: 62.4–111.6), 2 years: 92.3 pmol/L (IQR: 63.1–101.9); BL vs. 1 year: P = 0.017 and BL vs. 2 years: P = 0.019] in the overall analysis, but lost significance at 2 year follow‐up when assessed in paired subanalysis ( P = 0.116). Plasma pro‐SP levels remained comparable during the entire follow‐up [BL median: 78.3 pmol/L (IQR: 67.9–90.6), 1 year: 75.9 pmol/L (IQR: 58.6–96.3), 2 years: 79.7 pmol/L (IQR: 59.9–105.3); P = ns for both timepoints]. Biomarker patterns of ARNi patients were independent from baseline therapy, that is, ACEi or ARB ( P > 0.05 between groups). Conclusions: Although enkephalins and SP are known substrates of NEP, NEP inhibition by ARNi does not clearly affect the circulating precursors PENK and pro‐SP in HFrEF.